Agatha Christie's Miss Marple. Volume two. Sleeping murder. 4:50 from Paddington [videorecording (DVD)] - Christie, Agatha, 1890-1976; Hickson, Joan, 1906-1998; Alexander, Geraldine; Moulder-Brown, John; Treves, Frederick, 1925-2012; Anderson, Jean, 1907-2001; Davies, John Howard, 1939-2011; Mole, Juliette; Beames, David; Bruce, Mona, 1924-2008; Blane, Nicholas (DVD classics., 2001)
Sleeping murder: When Giles and Gwenda Reed move into their dream house in a seaside resort Gwenda is haunted by the vision of a body in the hall. Miss Marple uses her keen intuition to solve the murder of Gwenda's stepmother that took place in the house while Gwenda was living there during her childhood.